Aquaporin-4 positive neuromyelitis optica spectrum disorders secondary to thrombopenic purpura: A case report. Issue 2 (January 2017) - Wang, Ying; Gong, Qiaoyun; Zhu, Mingqin; Lu, Chao; Sun, Li; Feng, Jiachun; Zhang, Hongliang
Abstract: Rationale: Neuromyelitis optica spectrum disorders (NMOSD) is considered as an immune-mediated disorder in the central nervous system (CNS). Numerous autoimmune diseases are frequently complicated with NMOSD and distinct clinical characteristics are noted in NMOSD patients with other autoimmune diseases. However, to our best knowledge, co-occurrence of NMOSD and thrombopenic purpura is rarely identified. Patient concerns: We presented a rare case of a 72-year-old female with 6-year history of thrombopenic purpura, and 1-month history of blurred vision as well as chest zonethesia. Anti-aquaporin-4 (AQP4) antibodies was positive in the serum of the patient. Diagnoses: With the addition of laboratory findings, iconography findings and physical examination results, the diagnosis of NMOSD was established according to the most recent diagnostic criteria. Interventions and outcomes: With the treatment of intravenous immunoglobulin (IVIg), the patient felt better at discharge without changing of expanded disability status scale (EDSS) score. Lessons: The case indicates that NMOSD could co-occur with thrombopenic purpura. The disturbance of immune system balance may explain this overlap. Further studies are warranted to reveal the mechanism and to explore whether patients with NMOSD with and without thrombopenic purpura have distinct clinical feature, drug responsiveness or prognosis.